أحكام العضو البشري المزروع في أبواب الطهارة - زتون, خريف (جامعة الوادي - University of Eloued, 2019)
يدرس هذا المقال الأحكام الفقهيّة لنازلة نقل العضو البشري وإعادة زراعته؛ حيث يتطرّق لبحث حكم العضو البشري بعد إعادة زراعته من حيث طهارته ونجاسته، مستقصيا آراء الفقهاء المختلفة وأدلتهم التي استندوا إليها. كما يبحث حكم غسله في الوضوء والغُسل، إن وقع في محلّ فرض، وحكم المسح عليه إن كان ممّا يطلب مسحه في التيمّم. وأخيرا، يتعرّض البحث إلى حكم الملامسة به، وأثرها في نقض الطهارة. This article examines the fiqh provisions for the transfer and replantation of human organs. Where he deals with the study of the rule of the human organ after its re-implantation in terms of its purity and impurity, by mentioning the different opinions of the jurists and their evidence on which they relied. It also showed the ruling on washing the transplanted organ during Ablution and Washing ( Wudu and Ghusl), as well as the ruling on wiping it during Tayammum. Finally, she touched upon a statement of the ruling on touching by transplanted organ, and its effect on invalidating purity (Ṭahāra).
مقال
Keywords: العضو البشري؛ زراعة؛ الطهارة؛ الوضوء؛ الغسل؛ التيمم; Human organ; transplantation; purity (Ṭahāra); Ablution (Wudu); Washing (Ghusl); Tayammum.